The Effect of B Type Gelatine (Beef Gelatine) used on The Water Holding Capacity, Melting Time and Organoleptic Quality of Frozen Yoghurt (Faculty of Animal Science Universitas Brawijaya, 2007)
This research aims to find out and determine the proper concentration of beef gelatine which used to produce high quality of frozen yoghurt based on the water holding capacity, melting time and organoleptic quality (texture and taste). The frozen yoghurt was made from fresh milk, sugar, beef gelatine, and yoghurt starter (L. bulgaricus and S. thermophillus). The method which used an experiment with Randomized Block Design (RBD). The treatment consist of 4 level of gelatine concentration and 3 groups, i. e; P0 (0%), P1 (0.2%), P2 (0.4%), P3 (0.6%). Data analysis by analysis of variance and followed by Duncanâ€™s Multiple Range Test (DMRT) if there was any significant effect. The result of study showed that gelatine addition in frozen yoghurt gave water holding capacity average to treatment P0, P1, P2, P3 was 37.678%; 38.172%; 43.747%; melting time 126.000; 133.000; 147.333; 147.667 (minutes).The result of hedonic test to the frozen yoghurt texture was 5.750; 5.933; 6.167; 6.467 and taste was 6.583; 6.417; 6.417; 6.683; 6.950. It concluded that increasing of gelatine concentration gave significant effect on frozen yoghurt texture (P<0.05), did not gave the significant effect (P>0.05) on water holding capacity, melting time and taste of frozen yoghurt. It suggested to use 0.6% gelatine.Â Key words : frozen yoghurt, water holding capacity, melting time, gelatine. Â